Modelos de proteção comercial: uma resenha - Colistete, Renato [UNESP]; Menezes, Jarbas Dantas [UNESP] (Editora 34, 2019)
Protectionism has been an enduring source of international disputes since at least the nineteenth century. In the last decades, an array of nontariff barriers has created a new global phenomenon, the so-called New Protectionism, which once more shows the strength of the forces leading to the adoption of trade barriers by nations. This article aims to review representative analytical models which deal with the causes of protectionism. First, the article discusses historical political economy models and their focus on social groups, institutions and historical analysis. Second, the article addresses positive political economy models which bring organizations, interests and social actors into the framework of rational choice.

O protecionismo tem sido uma fonte permanente de disputas internacionais desde pelo menos o século XIX. Nas últimas décadas, uma série de barreiras não-tarifárias criou um novo fenômeno global, o chamado Novo Protecionismo, que mais uma vez mostra a eficácia das forças que levam à adoção de barreiras comerciais por parte das nações. Este artigo tem como objetivo revisar modelos analíticos representativos que lidam com as causas do protecionismo. Primeiro, o artigo discute modelos históricos de economia política e seu foco em grupos sociais, instituições e análises históricas. Em segundo lugar, o artigo aborda modelos de economia política positiva que trazem organizações, interesses e atores sociais ao quadro da escolha racional.
Models of commercial protection: a review
Keywords: Trade protection; political economy models; rational choice; historical political economy; Proteção comercial; modelos de economia política; escolha racional; economia política histórica